Determinação de fontes de hidrocarbonetos policíclicos aromáticos e alifáticos em sedimentos de ambientes aquáticos - Yamada, Thaís Mariana (2006)
Numerical values of polycyclic aromatic hydrocabons and n-alkanes distribution indexes of sediments are important tools to elucidate the origins of hydrocarbons mixtures. Polycyclic aromatic ratios are sensitive indicators of petrogenic and pyrogenic inputs, while n-alkanes distribution usualy discriminates biogenic from petrogenic sources. The study area of this work includes the Ibirité Reservoir and it´s tributaries, located in the Belo Horizonte metropolitan area, a site strongly affected by a petroleum refinary from Petrobras, but where an important industrial park is also present. Sampling was carried out in November 2005, at 12 stations located on Ibirité Reservoir, Pintados and Ibirité streams. The sediment samples were extracted in ultrasonic bath, purified in chromatographic columns and analysed by GC/MS. The studied compounds were polycyclic aromatic hydrocarbons, normal and isoprenoids alkanes. The total concentrations varied from 33.66 to 772.61 ng g-1. Despite of these low concentration values as compared to other aquatic environment, the Ibirité Reservoir showed strong inflluence from anthropic activities, reflected on petrogenic and pyrogenic hydrocarbons mixtures. The biogenic hydrocarbons, mainly derived from aquatic and terretrial higher plants, also showed its contribution as a result of algal blooms and extensive aquatic macrophyte banks typically found in the reservoir. Besides, the presence of unresolved complex mixtures in all chromatograms, points out to a significant contribution of petrogenic sources. Contamination of some sediment sample detectect in this study by polycyclic aromatic hydrocarbons migth suggest that occasional adverse effects to the organisms in this water body may occur. The sampling station of Taboões I stream was the only one site that petrogenic controbuition was not detected. However, the site that was considered as a reference site, showed that it suffers, already, influences from burned fossil fuel from industries and automobiles from the nearby Belo Horizonte metropolitan area.